2000
DOI: 10.1007/s1010599b0002
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Model of Large Magnetostrain Effect in Ferromagnetic Shape Memory Alloys

Abstract: A quantitative model describing large magnetostrain effect observed in several ferromagnetic shape memory alloys such as Ni2MnGa is briefly reported.The paper contains an exact thermodynamic consideration of the mechanical and magnetic properties of a similar type materials. As a result, the basic mechanical state equation including magnetic field effect is directly derived from a general Poisson's rule. It is shown that the magnetic field induced deformation effect is directly connected with the strain depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 9 publications
1
52
0
Order By: Relevance
“…The last model has been also successfully applied to explain quantitatively the results of experimental study of large magneto-strain effects in IS^MnGa earlier obtained in [2]. In particular, according to our model estimation made in [3] a giant magneto-strain value can be achieved only in materials with very low (< 2 MPa) twinning stress values. Mechanical testing results obtained for giant magneto-strain Ni-Mn-Ga samples have completely confirmed these estimations.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…The last model has been also successfully applied to explain quantitatively the results of experimental study of large magneto-strain effects in IS^MnGa earlier obtained in [2]. In particular, according to our model estimation made in [3] a giant magneto-strain value can be achieved only in materials with very low (< 2 MPa) twinning stress values. Mechanical testing results obtained for giant magneto-strain Ni-Mn-Ga samples have completely confirmed these estimations.…”
Section: Introductionmentioning
confidence: 59%
“…In this case, the main thermodynamic driving forces should have a magnetic nature and be connected with high magnetization anisotropy and significant differences in magnetization free energies for different twin variants of martensite [1][2][3][4][5][6][7]. For instance, Fig.l shows an example of giant 5% magneto-strain effect associated with the direct and reverse magnetic-field-induced transformation between two single twin variants in Ni 4 8Mn 3 oGa22 sample.…”
Section: Magnetic Driving Forces and Twin Boundary Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the control of shape-memory properties by application of an external magnetic field is a principle for operation of the recently developed actuator materials. 20,21 In Cu-Al-Mn the martensitic transition exists 14 only for compositions that are very far from the stoichiometry (Cu 2 AlMn) where the L2 1 ordered phase is paramagnetic. 22 Nevertheless, the influence of magnetism coming from Mn has been revealed in several experiments.…”
Section: Introductionmentioning
confidence: 99%